Long‐Term Effects of an Oral Rehabilitation Programme on the Oral Function of Male Patients With or Without Tongue Cancer - Lin, Pei‐Chen; Wang, Wen‐Chen; Kao, Yu‐Hsun; Matsuo, Koichiro; Lin, Ying‐Chu; Huang, Hsiao‐Ling (Journal of oral rehabilitation, 2025)
Postoperatively, patients with oral cancer experience chewing difficulties due to oral function disorders. This study aimed to evaluate the effects of an oral rehabilitation programme for improving oral function in patients with or without tongue cancer. We recruited patients with tongue cancer and those without tongue cancer in a medical centre. All patients underwent an oral rehabilitation programme, including oral hygiene and oral exercise training for 60 min by a dental hygienist, and they were reminded to perform these oral exercises during their monthly follow-up appointments. Data on oral diadochokinetic (DDK), tongue pressure and maximum mouth opening were collected at baseline and follow-ups. Linear regression with generalised estimating equations was performed to analyse oral functions between the tongue and non-tongue cancer groups over time. Patients in the tongue cancer group showed greater improvement for/pa/syllables (β = 4.67, effect size (ES) = 0.83, p = 0.025), /ta/syllables (β = 3.67, ES = 0.90, p = 0.024), and/ka/syllables (β = 5.02, ES = 0.96, p = 0.007) in oral DDK at 6-month follow-up than the non-tongue cancer group. A lower anterior tongue pressure was observed in the tongue cancer group at the 6-month follow-up than in the non-tongue cancer group (β = -10.30, ES = 1.15, p = 0.003). The oral rehabilitation programme was effective in improving the oral DDK rate after a 6-month intervention for patients with tongue cancer, while patients without tongue cancer exhibited a notable increase in tongue pressure.